Desenvolvimento de um protótipo de uma câmara de cultivo de plantas - Silva, Layane (2020)
Growing plants demands time and specific knowledge, which may present a hindrance for the city dweller, resulting in an underestimated use of urban areas. Developing a grow device, which mimics the required environmental conditions for plants, would reduce efforts in the maintenance of home gardens and would favor food production in the cities. The present work aimed the construction of a prototype for growing plants through the optimization of light and temperature, two of the most relevant parameters in the plant production. The equipment had outside dimensions of 70 cm (H) x 15 cm (d) and it was built from a PVC tube. The cooling system had an exhaust fan on the top side and four holes on the bottom side for air entrance. The light system was designed with LEDs in the red, blue and white spectrum, connected to a potentiometer for individual spectrum regulation. Two versions of the prototype were tested, which differ from each other mostly in terms of material (with or without an aluminum layer), in the quantity and types of LED, and in the position of the light source (on stages in the second version). Intensity and quality of the resulting light were measured in different experimental designs. A temperature profile was built for different environmental conditions with support of geostatistics. The final version achieved a light intensity of approximately 140 μmol m 2 s -1 and an average inner temperature of 24°C, with all lights on on the first stage and a controlled environment at 19°C. The effectiveness of the grow prototype was demonstrated by growing a healthy and capable of flowering Arabidopsis thaliana.